2007
DOI: 10.1037/0022-0663.99.3.545
|View full text |Cite
|
Sign up to set email alerts
|

Stereotype threat among schoolgirls in quasi-ordinary classroom circumstances.

Abstract: There is ample evidence today in the stereotype threat literature that women and girls are influenced by gender-stereotyped expectations on standardized math tests. Despite its high relevance to education, this phenomenon has not received much attention in school settings. The present studies offer the 1st evidence to date indicating that middle school girls exhibit a performance deficit in quasi-ordinary classroom circumstances when they are simply led to believe that the task at hand measures mathematical sk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
133
1
7

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 282 publications
(150 citation statements)
references
References 106 publications
9
133
1
7
Order By: Relevance
“…Three published studies found stereotype threat effects during middle school (Ambady et al, 2001;Huguet & Regner, 2009;Muzzatti & Agnoli, 2007, Experiment 2), one published study showed mixed results (Huguet & Regner, 2007, Study 2), and one published study (Huguet & Regner, 2007, Study 1) and one unpublished dissertation (Good, 2001) showed no evidence of a stereotype threat effect. Huguet and Regner (2007, Study 2) found that girls who completed the task in a mixedgender setting were impacted by stereotype threat but those taking it in a same-gender setting were not.…”
Section: Empirical Findingsmentioning
confidence: 99%
See 1 more Smart Citation
“…Three published studies found stereotype threat effects during middle school (Ambady et al, 2001;Huguet & Regner, 2009;Muzzatti & Agnoli, 2007, Experiment 2), one published study showed mixed results (Huguet & Regner, 2007, Study 2), and one published study (Huguet & Regner, 2007, Study 1) and one unpublished dissertation (Good, 2001) showed no evidence of a stereotype threat effect. Huguet and Regner (2007, Study 2) found that girls who completed the task in a mixedgender setting were impacted by stereotype threat but those taking it in a same-gender setting were not.…”
Section: Empirical Findingsmentioning
confidence: 99%
“…The testing session took approximately 40 min. Told that the task was a "geometry test" Told that the task was a "memory game" Huguet & Regner (2007), Study 2; Huguet & Regner (2009) Told that the task measured ability in geometry Told that the task measured ability in drawing Stricker & Ward (2004) Checked gender before test Checked gender after test Keller (2007); Keller & Dauenheimer (2003) Read that the test showed gender differences Read that the test showed no gender differences a Cruz-Duran (2009) Shown research evidence that men do better than women on math tasks Shown research evidence that there are no gender differences on math tasks a Dinella (2004) Indicated gender at beginning of tests and told that it is important to do because gender differences are sometimes present on tests Indicated gender at beginning of test Good (2001) Told that the test will show how smart they are in math Told that the problems are to see how students think about math and reading Picho & Stephens (2012) Told that the test assesses students' ability in math and that there are gender differences on the test…”
Section: Methodsmentioning
confidence: 99%
“…1) that had no particular meaning, and then 5 minutes to reconstruct it from memory on paper. This task, which has already proved successful in detecting ST (Huguet & Régner, 2007), taps into skills (i.e., visual-perceptual and visual-spatial) as well as cognitive and meta-cognitive processes (attention, organization, and strategy use) that are basic components of academic performance (Kirkwood, Weiler, Bernstein, Forbes, & Waber, 2001). Students were either told the test would measure their ability in geometry or in drawing.…”
Section: Methodsmentioning
confidence: 99%
“…Despite or perhaps because of long-standing scholarly interest in stereotype threat, there is competing evidence regarding whether stereotype threat explains real-world differences in group outcomes. Although some work suggests that stereotype threat explains real-world differences in achievement (Good, Aronson, and Inzlicht 2003;Huguet and Régner 2007;Walton and Spencer 2009), other work has raised questions about the straightforward application of stereotype threat explanations outside the laboratory setting (Cullen, Hardison, and Sackett 2004;Morgan, Mehta, and Research Library Core 2004;Müller and Rothermund 2014;Stricker and Ward 2004;Wax 2009;Wei 2012). At the very least, recent work has emphasized that the effects of stereotype threat by race depend on contextual moderators such as the racial composition of a given school (Hanselman et al 2014) or local understandings of race (Herman 2009).…”
Section: Research-article2018mentioning
confidence: 99%